2005
DOI: 10.1097/01.mlg.0000184325.44968.b1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Laryngeal Irritation Signs Associated with Reflux in Asymptomatic Volunteers: Impact of Endoscopic Technique (Rigid vs. Flexible Laryngoscope)

Abstract: Several signs of posterior laryngeal irritation (e.g., interarytenoid bar, erythema of the medial wall of the arytenoids), which are generally considered to be signs of laryngopharyngeal reflux, are present in a high percentage of nonsymptomatic individuals, raising question about their diagnostic specificity. In addition, these signs were more often detected with flexible than with rigid laryngoscopes, suggesting that flexible laryngoscopy is more sensitive but less specific in identifying laryngeal tissue ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(115 citation statements)
references
References 13 publications
4
107
1
3
Order By: Relevance
“…Moreover, there was no significant difference between the positive and negative pH groups for RFS scores. These results match some other studies that reported the presence of LPR-related laryngeal signs in healthy volunteers with no voice problems [21,29,30,31,32,33,34,35]. The results of these studies indicate that most of the laryngoscopic findings reported in LPR patients are nonspecific and the laryngoscopic diagnosis of LPR is more likely subjective.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, there was no significant difference between the positive and negative pH groups for RFS scores. These results match some other studies that reported the presence of LPR-related laryngeal signs in healthy volunteers with no voice problems [21,29,30,31,32,33,34,35]. The results of these studies indicate that most of the laryngoscopic findings reported in LPR patients are nonspecific and the laryngoscopic diagnosis of LPR is more likely subjective.…”
Section: Discussionsupporting
confidence: 77%
“…Laryngoscopic fi ndings, especially edema and erythema, are oft en used to diagnose refl ux-induced laryngitis ( 134 ). It should be pointed out that laryngoscopy revealed one or more signs of laryngeal irritation in over 80 % of healthy controls in a well-done prospective study ( 135 ). Moreover, in a study of fi ve ENT (ear, nose, and throat) physicians who blindly evaluated 120 video recordings of laryngoscopy exams, concordance among physicians was low for edema, erythema, as well as likelihood and severity of laryngopharyngeal refl ux; similarly, intra-rater reliability was extremely variable for these fi ndings ( 136 ).…”
Section: Gerd Refractory To Treatment With Ppismentioning
confidence: 99%
“…The comparison of findings between flexible and rigid laryngoscopes on healthy volunteers, laryngeal signs such as arytenoid erythema and pseudosulcus were more like- Table 5. Relation between the reflux symptom index and individual variables from the reflux finding score ly to be detected with a flexible rather than a rigid endoscope (23). For this reason, reliability of RFS with flexible laryngoscope should also be investigated with future studies.…”
Section: Discussionmentioning
confidence: 99%